Investigation of the Stiffness and Ductility of Pre-Cracked RC Beams after repairing with CFRP using Different Strengthening Methods - Yahya Turki, Abbas; Al-Farttoosi, Mahdi Hameed (Engineering, Technology & Applied Science Research, 2023)
This study investigated the stiffness and ductility of rectangular Reinforced Concrete (RC) beams. The beams were obtained through an experimental program that included one reference and eight RC beams, divided into two separate groups strengthened with Externally Bonded Reinforcement (EBR) and Near-Surface Mounted (NSM) reinforcement in flexural using Carbon Fiber Reinforced Polymer (CFRP) laminate after they were pre-cracked or damaged at different levels. The comparison results of the reference and the strengthened beams showed that the latter had a higher degree of stiffness. The stiffness in the yielding stage increased by 6.43% to 19.81% for the EBR-strengthened group and by 31.08% to 105.8% for the NSM-strengthened group. At the 140 kN loading stage, the stiffness increased by 33 to 101.5% for the EBR-strengthened group and by 136.5% to 332.25% for the NSM-strengthened group. At the ultimate load stage, the stiffness increased by 12.72% to 46.13% for the EBR-strengthened group and by 56.85% to 122.94% for the NSM-strengthened group. On the other hand, the comparison revealed that the ductility of the reference beam was much better than that of the reinforced beams.